Reimagining academic conferences: Toward a federated model of conferencing. Issue 2 (April 2022) - Etzion, Dror; Gehman, Joel; Davis, Gerald F
What should the post-COVID conference look like? In our attempt to answer this question, we first describe the primary functions and affordances of conferences. Our frank appraisal reveals the breadth of reasons why academics attend conferences, and how conference attendance often blends personal and professional motivations. We also elaborate some of the shortcomings of in-person conferences, spanning personal, professional, and societal concerns. Recent alternative (virtual) formats for convening scholars provide means for alleviating some of these shortcomings, but do not seem entirely up to the task of providing a fully satisfactory solution to all that conferencing can be. Moreover, we extrapolate from prior history and ongoing trends to predict that technological solutionism to conferencing is likely to unleash both positive and negative dynamics, some of which will exacerbate current ills in our profession. We then sketch out a values-based approach that can serve as a basis for reimagining academic conferences. This vision promotes a federated model of conferencing, grounded in principles of inclusion, diversity, community, and environmental stewardship.